2009
DOI: 10.1002/bsl.889
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of impulsive aggression in correctional settings

Abstract: The study supports the value of DBT-CM for management of aggressive behaviors in prison settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 38 publications
3
64
0
5
Order By: Relevance
“…25 In persons with impulsive behavior problems, dialectical behavioral therapy group sessions and individual coaching resulted in some improvement in mental health compared with dialectical behavioral therapy group sessions and weekly case management. 121 In contrast, 4 other studies of psychotherapies found no differences between intervention and control groups. 86,95,96,141,144 In women with PTSD related to interpersonal victimization, there was no difference in PTSD or overall mental health status between persons randomized to group psychotherapy to enhance affect regulation without trauma memory processing or to supportive group therapy.…”
Section: Mental Health Interventionsmentioning
confidence: 89%
See 2 more Smart Citations
“…25 In persons with impulsive behavior problems, dialectical behavioral therapy group sessions and individual coaching resulted in some improvement in mental health compared with dialectical behavioral therapy group sessions and weekly case management. 121 In contrast, 4 other studies of psychotherapies found no differences between intervention and control groups. 86,95,96,141,144 In women with PTSD related to interpersonal victimization, there was no difference in PTSD or overall mental health status between persons randomized to group psychotherapy to enhance affect regulation without trauma memory processing or to supportive group therapy.…”
Section: Mental Health Interventionsmentioning
confidence: 89%
“…25,43,68,69,121,134 Participants in 4 interventions experienced less anxiety and depression relative to those in control groups with no intervention: adolescent boys with PTSD in shortterm cognitive processing therapy 68 ; adult women with a history of interpersonal violence in group trauma treatment therapy 69 and traumatic incident reduction therapy 134 ; and vulnerable adolescents in group social problem-solving therapy. 43 Individual cognitivebehavioral therapy and combined individual and group cognitive-behavioral therapy both led to greater improvements in overall mental health in men, with the combined group showing greater efficacy than the individual group for most outcomes.…”
Section: Mental Health Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified DBT programme made up of a 16-week DBT skills group, followed by random assignment to DBT coaching or an individual case management condition for eight weeks, was delivered to female and male offenders with impulsive behavioural problems, across the Connecticut State prisons (Shelton, Sampl, Kesten, Zhang, & Trestman, 2009). Over the course of the study, Shelton et al, found no significant changes in participants' standardised measure scores.…”
Section: Adaptation To the Prison Settingmentioning
confidence: 98%
“…Further, significant improvements were noted on a measurement of coping skills, problem solving and accepting responsibility as well as significant decreases in disciplinary tickets from pre-to post-DBT skills group assessment. Shelton, Sampl, Kesten, Zhang, and Trestman (2011) completed a secondary analysis of 38 male adolescents from the Shelton et al, (2009) study and noted significant changes in physical aggression, distancing coping methods and number of disciplinary tickets for behaviour.…”
Section: Adaptation To the Prison Settingmentioning
confidence: 99%